E-INFORMATION SYSTEM DESIGN OF STUDENT ADMISSION IN AMERICAN INDONESIAN EDUCATIONAL INSTITUTION CIJANTUNG BRANCH - Oktaviani, Anggi; Sarkawi, Dahlia; Novianti, Deny; Amri, Achmad Chaerul (Kresnamedia Publisher, 2021)
Currently, companies, organizations and institutions are in dire need of the development of technology and information systems, especially information technology through the internet. The American Indonesian Education Institute, the Cijantung Branch, which until now has not yet been computerized. Currently, the registration process to become a student at the American Indonesian Education Institute Cijantung Branch is still manual, both from filling out forms provided by the American Indonesian Education Institute Cijantung Branch to becoming a student. Usually the data collection process is a bit hampered because the number of applicants is more than customer service and it is too difficult for customer service to read prospective student forms. This causes the service from the customer service of the American Indonesian Education Institute Cijantung Branch is not optimal. This study uses the waterfall model as a software development model. From the research conducted, it is expected to produce a new student acceptance control system that can assist customer service in collecting data on prospective students and managing prospective student forms. The design of the new student admission system is expected to be more effective and efficient. So it's good when registration can be completed in a short time. This system is also expected to minimize data collection errors made by customer service.